Challenges and facilitators of hospice decision-making: a retrospective review of family caregivers of home hospice patients in a rural US–Mexico border region—a qualitative study - Eunjeong Ko; Dahlia Fuentes; Savitri Singh-Carlson; Frances Nedjat-Haiem (BMJ Open)
Objectives Hospice care (HC) is seen as a comprehensive approach, that enhances quality of end-of-life (EOL) care, for terminally ill patients. Despite its positive aspects, HC enrolment is disproportionate for rural patients, who are less likely to use HC in comparison to their urban counterparts. The purpose of this study was to explore decision-making experiences, related to utilisation of HC programmes from a retrospective perspective, with family caregivers (FCGs) in a rural US–Mexico border region.Design This qualitative study was conducted from May 2017 to January 2018 using semistructured face to face interviews with FCGs. Data were analysed using thematic analysis.Setting The HC programme was situated at a local home health agency, located in rural Southern California, USA.Participants Twenty-eight informal FCGs of patients who were actively enrolled in the HC programme agreed to participate in the study.Results Conversation about HC as an option was initiated by home healthcare staff (39.3%), followed by physicians (32.1%). Emerging themes related to challenges in utilisation of HC and decision-making included: (1) communication barriers; (2) lack of knowledge/misperception about HC; (3) emotional difficulties, including fear of losing their patient, doubt and uncertainty about the decision, denial and (4) patients are not ready for HC. Facilitators included: (1) patient’s known EOL wishes; (2) FCG-physician EOL communication; (3) the patient’s deteriorating health and (4) home as the place for death.Conclusions HC patients’ FCGs in this rural region reported a lack of knowledge or misunderstanding of HC. It is recommended that healthcare providers need to actively engage family members in patient’s EOL care planning. Optimal transition to an HC programme can be facilitated when FCGs are informed and have a clear understanding about patients’ medical status along with information about HC.